Pelatihan Pembuatan Arang Tempurung Kelapa Menggunakan Retort di Sawah Lebar Baru, Kota Bengkulu - Hendri Hestiawan; Nurul Iman Supardi; Angky Puspawan (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2024)
Coconut shell waste has not been utilized into useful ones. Its condition is a potential problem for the environment. Coconut shells can be made into charcoal using a retort. Training on making charcoal from coconut shells in a retort furnace was given to community groups in Sawah Lebar Baru, Bengkulu City. The activity includes several stages: observation, preparation, implementation and evaluation of the activities carried out. The implementation involved lecturers and students from the Mechanical Engineering Study Program, Faculty of Engineering, University of Bengkulu. Participants from the community were quite helped by the presence of students so that they were very enthusiastic and played an active role during the activity. At the evaluation stage, an assessment was given to participants in two stages, pre-test and post-test. The assessment results showed that the activity was able to increase participants' understanding of the material from 52% to 80%.